A Sordid Tale of Bile and Bowel: A Case Report - Abhay K. Kattepur; Sreeramulu P. Nadipanna; H. L. Deepak; T. N. Suresh; Srinivasan Doraiswamy; D Aswathappa (World Journal of Colorectal Surgery)
Synchronous tumors of gall bladder and colon cancer are rare, and the underlying genetic, environmental, and immunological factors could play a role in the development of such tumors. Till date, only a few cases of synchronous gall bladder and colonic malignancies have been reported. A 60-year-old lady presented with sub-acute onset of colicky pain in the abdomen and vomiting. Imaging showed the presence of thickening in the ileocecal junction along with a thickened gall bladder. A provisional diagnosis of gall bladder tumour with ileocecal tuberculosis or a synchronous colonic malignancy was made. Laparotomy revealed synchronous tumors in the gall bladder and caecum. Radical cholecystectomy with radical right hemicolectomy was performed. The final histopathology report confirmed the presence of two independent malignancies. A tailored treatment approach for both sites based on clinical findings and anticipated outcomes must be considered. Further immunohistochemical studies must be conducted to confirm the presence of dual malignancies. Metastases from one site to the other should be ruled out.